Receipt of opioid analgesics by HIV-infected and uninfected patients. - Edelman, E Jennifer; Gordon, Kirsha; Becker, William C; Goulet, Joseph L; Skanderson, Melissa; Gaither, Julie R; Brennan Braden, Jennifer; Gordon, Adam J; Kerns, Robert D; Justice, Amy C; Fiellin, David A (Journal of general internal medicine, 2013)
Opioids are increasingly prescribed, but there are limited data on opioid receipt by HIV status.
Keywords: Acute Pain; Adult; Analgesics, Opioid; Chronic Pain; Cross-Sectional Studies; Drug Administration Schedule; Drug Prescriptions; Drug Utilization; Female; HIV Infections; Humans; Male; Middle Aged; Pain; Pain Management; Sex Factors; United States; Veterans